Analisis rasch sebagai teknik untuk menyemak ciri psikometrik item soalan pendidikan Islam - Ab Rahim, Saiful Adli; Jamaluddin, Shahrir; Abdul Aziz, Azrillah; Abu Kassim , Noor Lide (Kementerian Pendidikan Malaysia, 2012)
Achievement test is a tool to measure attainment of teaching and learning objectives, monitor learning progress, and diagnose students' learning difficulties. And accuracy in measurement is essential to help teachers/practitioners in designing effective intervention stategies. In order to arrive at accurate and valid measures of student achievement, robust statistical methods are necessary to assess the quality of test items. This article illustrates how the Rasch Measruement Model is used to examine the psychometric characteristics of an Islamic Education test, and ways in which to improve the accuracy and precision of the 40 items used in the test.